Children's psychology development - Ilias, Mohd Rahimman; Esa, Ahmad (Elixir International Journal, 2017)
The child is a gift given to each couple. Their growth process from children to adults plays an important role in shaping their personal qualities and behaviors. This reading is carried out in order to determine how the nature of the child is formed from a baby. This study emphasizes the child's development from the angle of cognitive and personality.